MSG WASTE BIOMASS CONCENTRATION ON MEMBRANE BIOREACTOR SUBMERGED - Agung Rasmito, Jenny Caroline, Yustia Wulandari M* (Jurnal Teknik Kimia, 2010)
The combination of submerged membrane bioreactor (BRMt) and activated sludge is onealternative that can provide a solution. The purpose of this study was to determine the effect oforganic load on the performance of the combination of activated sludge and membranesubmerged, know the effect of microorganism concentration on the performance of thecombination of activated sludge and membrane submerged. Membrane bioreactor Awash (BRMt)used has concentration of biomass to be used is 15,000 mg / L, 20,000 mg / L and 25,000 mg / L,and COD concentration of MSG wastewater used was 10,000 mg / L and 15,000 mg / L. CODload successfully diremove average for each variation of the COD load of up to 98%. Inwastewater treatment using membrane processes, fouling is one of the obstacles that can interferewith the performance of submerged membrane bioreactor, so that by the backflushing andbackwash is to help improve the performance of membrane separation process in the processing ofthe waste. This is indicated by the analysis results that meet the standard of quality standardsbased on the Liquid Waste Kep. Gub No.45 of 2002.Keywords: wastewater, waste MSG, submerged m